Development characteristics of loose karst collapse columns and their transformation effect on coal properties and coal quality - Heping LIU; Shuaifeng LYU; Xiao YANG; Chong CHEN; Zhangkai XIONG; Shuai MA (Meikuang Anquan)
Karst collapse column is one of the main geological factors that cause hidden disasters in many coal fields in North China. Especially, when the columns are soft and fractured, they will make great challenges to exploration, prevention, and safety production work in the coal mines. The penetrating relationship, distribution pattern, and internal structural characteristics of karst collapse columns in Xinliangyou Coal Mine in Huoxi Coalfield were revealed, and the transformation effect of collapse columns on edge coal seams were discovered, through on-site investigation, data statistics, sample microscopic identification, proximate analysis, and scanning electron microscopy analysis. Result shows that most of the exposed collapse columns in the coal mine are elliptical in plane, with an axis length of less than 30 m. The number of collapse columns in the lower coal group is much greater than that in the upper coal group, and the collapse columns that run through are distributed in clusters. Due to the small burial depth of the coal seam, weak compaction of the strata, and significant differences in mechanical properties between the coal seam and the roof, the collapse columns present an irregular funnel shape on the profile. The internal bonding of the columns is extremely weak, in which consist of loose accumulation of broken mudstone mixed with sandstone blocks. Additionally, influenced by the development of collapse column, the column are arranged outward in order as fracture zone, weathered oxygenized zone, transition zones, and normal coal seam zone. The transformation range of coal property and coal quality is within 5-10 m. From the column outward, the inorganic mineral content and ash yield of weathered oxygenized coal decrease. The weathered oxygenized coals contain a large amount of clay minerals with silicon and aluminum. As a marker property of the collapse column, the exposure of weathered oxygenized coal can provide new indications for close range advanced detection of the collapse columns.